A critical investigation into spontaneous combustion in coal storage bunkers - S. Govender; J. J. L. du Plessis; R. C. W. Webber-Youngman (The Southern African Institute of Mining and Metallurgy, 2021)
Spontaneous combustion (SC) is a cold oxidation reaction that generates heat, causing a temperature rise of the reactant and leading, with limited heat dissipation, to self-ignition of the reactant, which occurs without an external heat source. Although not limited to coal, the most significant hazard of SC are the fires that occur in coal mining operations around the world. These fires pose a serious risk to the safety of workers in the mines as well as adverse effects on the environment, and can affect the quality of life for current and future generations. We investigated the occurrence of SC in raw coal storage bunkers with the purpose of compiling a decision analyser for engineers designing or working with coal storage bunkers. Specific experts were interviewed from different backgrounds and companies, followed by field research at a coal mine. The important factors affecting the possibility of SC occurring were the type of coal supplied to the bunker, the mining practice, and physical conditions around the bunker. The information presented here will assist in reducing the SC risk in raw coal storage bunkers. These findings, together with the systematic decision analyser developed, will assist design engineers and mine personnel to take early preventative steps in managing SC. The decision analyser was tested for many different scenarios and gave good guidance on how to minimize and prevent SC in bunkers